Corrosion Rate of Black Chromium Coating Result of Electroplating on Copper - Hadi, Syamsul; Valeria, Sza Sya Monica; Adiwidodo, Satworo; Amrullah, Utsman Syah; Takwim, R.N. Akhsanu; Firmansyah, Hilmi Iman (INTEK: Jurnal Penelitian, 2020)
The problem faced is that the white chromium coating has a low selling value or aesthetic value than the black chromium layer which is more in demand, especially by the younger generation who prioritizes aesthetics. The purpose of the corrosion test was to determine the corrosion resistance ability of the black chromium coating resulting from the electroplating process on the relationship between the solution temperature and the immersion time of copper in a corrosive solution. Corrosion test methods include literature studies, field observations, weighing specimens, immersing specimens in corrosive solutions, weighing specimens, calculating corrosion rates, and data analyzing. Corrosion test results show that the higher the temperature of the solution and the longer the immersion time, the smaller the corrosion rate for the lowest conditions at 30oC and a duration of 5 minutes with a corrosion rate of 0.2004 mm/year and the highest conditions at a temperature of 50oC and a duration of 9 minutes at a rate of corrosion of 0.0108 mm/year.